Characterization of carbon nanotube field-effect transistor fabricated by direct growth method - Mohamed, Mohd Ambri; Asyadi Azam, Mohd; Kawabuchi, Hitoshi; Shikoh, Eiji; Fujiwara, Akihiko (2010)
We have fabricated carbon nanotube field-effect transistor by means of direct growth method and investigated their structural and transport characteristics. The FET shows ambipolar operation. We showed the current modulation by bias and gate voltage and its relation. The device operation is consistent with Schottky-type FET, and showed small value of activation energy.